1991
DOI: 10.1121/1.400523
|View full text |Cite
|
Sign up to set email alerts
|

Effects of focusing on the nonlinear interaction between two collinear finite amplitude sound beams

Abstract: A study of the propagation and interaction of two collinear finite amplitude sound beams, presented in a previous paper [Naze Tjo/tta et al., “Propagation and interaction of two collinear finite amplitude sound beams,” J. Acoust. Soc. Am. 88, 2859–2870 (1990)] is extended to include the effects of focusing. The validity of the parabolic equation when applied to strongly focused sound beams is discussed. Equations and algorithms based on a transformed parabolic equation are presented and used to compute the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(31 citation statements)
references
References 0 publications
0
29
0
1
Order By: Relevance
“…Apart from the lateral beam width, the axial focal region is smaller and more pronounced than with conventional 1.5 MHz ultrasound field generation. 48 When comparing the simulation results of the beam profiles to the experimental ones ͑Figs. 6 and 7͒, in general, very similar levels occur for all four frequency components ͑ex-cept for the focal region; see below͒.…”
Section: A General Principlementioning
confidence: 99%
“…Apart from the lateral beam width, the axial focal region is smaller and more pronounced than with conventional 1.5 MHz ultrasound field generation. 48 When comparing the simulation results of the beam profiles to the experimental ones ͑Figs. 6 and 7͒, in general, very similar levels occur for all four frequency components ͑ex-cept for the focal region; see below͒.…”
Section: A General Principlementioning
confidence: 99%
“…where k is the wavenumber, D is the focal length, a is the source radius, and z is the distance from the source [28]. The KZK equation was solved in the frequency domain using a finite-difference scheme that was a development of the Bergen code [29].…”
Section: B the Numerical Modelmentioning
confidence: 99%
“…It can be found that the pressure amplitude from SBE is slightly smaller than that from KZK model in the focal region and the maximum deviation is less than 3%, but both models are in good agreement in the axial distribution and beam patterns. Moreover, previous studies [3] validated effectiveness of KZK model for a parametric focusing source. Consequently, the focused parametric model of SBE is also good valid for a parametric focusing source on a concave spherical surface with a large aperture angle in the acoustic field.…”
Section: Numerical Examplesmentioning
confidence: 99%
“…However, these works were generally used to describe nonlinear interactions of a parametric planar sound source. Although effects of focusing on the parametric interaction between two focused beams generated by monochromatic sources was investigated with KZK equation, this model is more suitable for a weak focused ultrasound beam because that it derived under the paraxial approximation and the upper limit of the applicability is about for the half aperture angle [3].…”
Section: Introductionmentioning
confidence: 99%